Effect of Anti-IL17 Antibody Treatment Alone and in Combination With Rho-Kinase Inhibitor in a Murine Model of Asthma - Santos, Tabata M. dos; Righetti, Renato F.; Camargo, Leandro do N.; Saraiva-Romanholo, Beatriz M.; Aristoteles, Luciana R. C. R. B.; de Souza, Flávia C. R.; Fukuzaki, Silvia; Alonso-Vale, Maria I. C.; Cruz, Maysa M.; Prado, Carla M.; Leick, Edna A.; Martins, Milton A.; et al. (Frontiers in Physiology, 2018)
BACKGROUND: Interleukin-17 (IL-17) and Rho-kinase (ROCK) play an important role in regulating the expression of inflammatory mediators, immune cell recruitment, hyper-responsiveness, tissue remodeling and oxidative stress. Modulation of IL-17 and ROCK proteins may represent a promising approach for the treatment of this disease. OBJECTIVE: To study the effects of an anti-IL17 neutralizing antibody and ROCK inhibitor treatments, separately and in combination, in a murine model of chronic allergy-induced lung inflammation. METHODS: Sixty four BALBc mice, were divided into eight groups (n=8): SAL (saline-instilled); OVA (exposed-ovalbumin); SAL-RHOi (saline and ROCK inhibitor), OVA-RHOi (exposed-ovalbumin and ROCK inhibitor); SAL-anti-IL17 (saline and anti-IL17) OVA-anti-IL17 (exposed-ovalbumin and anti-IL17); SAL-RHOi-anti-IL17(saline, ROCK inhibitor and anti-IL17); OVA-RHOi-anti-IL17 (exposed-ovalbumin, anti-IL17 and ROCK inhibitor). A 28-day protocol of albumin treatment was used for sensitization and induction of pulmonary inflammation. The anti-IL17A neutralizing antibody (7.5 µg per treatment) was administered by intraperitoneal injection and ROCK inhibitor (Y-27632) intranasally (10 mg/kg), one hour prior to each ovalbumin challenge (day 22, 24, 26 and 28). RESULTS: Treatment with the anti-IL17 neutralizing antibody and ROCK inhibitor attenuated the percentage of maximal increase of respiratory system resistance and respiratory system elastance after challenge with methacholine and the inflammatory response markers evaluated (CD4+, CD8+, ROCK1, ROCK2, IL-4, IL-5, IL-6, IL-10 IL-13, IL-17, TNFα, TGFβ, NF-κB, dendritic cells, iNOS, MMP-9, MMP-12, TIMP-1, FOXP3, isoprostane, biglycan, decorin, fibronectin, collagen fibers content and gene expression of IL-17, VAChT and arginase) compared to the OVA group (p<0.05). Treatment with anti-IL17 and the ROCK inhibitor together resulted in potentiation in decreasing the percentage of resistance increase after challenge with methacholine, decreased the number of IL-5 positive cells in the airway, and reduced IL-4, IL-5, CD8+, FOXP3, ROCK1 and ROCK2 positive cells in the alveolar septa compared to the OVA-RHOi and OVA-anti-IL17 groups (p<0.05). CONCLUSION: Anti-IL17 treatment alone or in conjunction with the ROCK inhibitor, modulates airway responsiveness, inflammation, tissue remodeling and oxidative stress in mice with chronic allergic lung inflammation.